Determinan Modal Manusia terhadap Produktivitas Pemanen Kelapa Sawit: Bukti Empiris dari Analisis Data Panel - Riyanto, Agus; Wijayanti, Irene Kartika Eka; Putri, Dindy Darmawati (Fakultas Pertanian Universitas Tanjungpura, 2026)
Human Capital Determinants of Oil Palm Harvester Productivity: Evidence from Panel Data Analysis. Harvester productivity is a key determinant of operational performance in oil palm plantations, where variations in individual output reflect differences in human capital characteristics. This study aims to examine the effects of human capital, represented by age, length of service, and regional origin, on oil palm harvester productivity. The research was conducted at PT Karunia Kencana Permaisejati, Central Kalimantan, using monthly panel data from December 2024 to November 2025 covering 118 harvesters. A panel data regression approach with a random effects model was employed to capture both individual and temporal variations. The results indicate that age has a positive and statistically significant effect on productivity, suggesting that accumulated experience enhances work efficiency, although the magnitude remains limited due to physical constraints. In contrast, length of service has a negative and significant effect, revealing a non-linear relationship characterized by diminishing productivity beyond an optimal tenure period. Regional origin also significantly influences productivity, with harvesters from East Java outperforming others. These findings confirm that human capital plays a crucial but non-linear role in determining labor productivity and contribute to the literature by providing panel-based empirical evidence to support more effective workforce management strategies in plantation systems.